Field assessment on the influence of RhizoVital® 42 fl. and Trichostar® on strawberries in the presence of soil-borne diseases. (June 2017) - Bisutti, I.L.; Pelz, J.; Büttner, C.; Stephan, D.
Abstract: Strawberries are one of the most popular fruits in Germany. However, an expansion of the cultivation area, especially for organic strawberry production, is limited due to the high yield losses caused by diseases and arthropod pests. Therefore, the two soil strengthener RhizoVital ® 42 fl. and Trichostar ® were evaluated for their efficacy in stabilizing strawberry yields in the presence of soil-borne diseases. First, an integration of antagonists in an IPM strategy was proven by testing their compatibility with synthetic pesticides. When mixed for a maximum of four hours only few fungicides reduced germination of the antagonistic fungus contained in Trichostar ® . The germination of the bacterial antagonist (RhizoVital ® 42 fl.) was not influenced by any tested synthetic pesticide used in this study. Afterwards, the microbial based products were tested in two commercial strawberry fields in the Rheine-Main area, in which Verticillium -wilt was found. In one field, with just one treatment of Trichostar ® in 2013, the yield increase in 2013 and 2014 was 8 and 9%, respectively. On the second field, RhizoVital ® 42 fl. was applied both years and the increase was about 6% each year. Our results demonstrate that beneficial micro-organisms can promote health and can stabilize or increase yield of strawberries under field conditions. Integration of these organisms in IPM strategies seems to be possible. Highlights: RhizoVital ® 42 fl. increased strawberry yield of about 6% in two consecutive years. Trichostar ® increased strawberry yield of about 8% in two consecutive years. In general a combination of synthetic pesticides with the two soil strengtheners is possible.